Pemanfaatan Bantuan Program Keluarga Harapan untuk Menyukseskan Wajib Belajar XII Tahun di Kecamatan Pusako Siak - Nuryanti Nuryanti (Indonesian Journal of Islamic Educational Management, 2019)
The purpose of this study was to determine the extent to which the utilization  of the Family Assistance Program (PKH )was expected to be successful in 12 years of  compulsory education in the sub-district  of Pusako Kabupaten Siak . The population in this study were all heads who received PKH assistance in the sub-district  of Pusako kabupaten Siak. The results of the study showed that PKH assistance funds were given to succeed the 12 year compulsory education in the sub district of Pusako were very satisfying. PKH assistance was able to explain and influence the educational participation of very poor household children in the sub distrct Pusako Siakreaching 96,8 percent and 3,2 percent influenced by other variables outside of this research model. PKH assistance provision should be on target and really aimed at improving children’s aducation.